Digital revolution in healthcare: Potential tool for achieving health equity in Bangladesh - Purabi, Nowsheen Sharmin (International Journal of Human and Health Sciences (IJHHS), 2019)
Men’s engagement in women’s sexual and reproductive healthcare as well as responsible parenthood is a demand of time in countries like Bangladesh, where men play a vital role, when it comes to the issue of women’s ability to seek healthcare. Yet, we couldn’t reach a point, where our men are wellequipped with proper healthcare information to assist their partners in a specific health complication and fully participate to take a decision on their health and wellbeing. But, if they can be aware and motivated about the importance of their active involvement in family’s healthcare using ICT tools, they could definitely help their partners to take effective decision in emergency. Ensuring the use of low cost intervention like ICT tools for receiving health information will also help achieving the vision of health equity, by engaging all, regardless of gender or class barriers. Objective: The main objective of this paper is to assist the healthcare professionals and development partners, who are involving with advocacy through e-health awareness programs using ICT tools, to formulate their coordinated next plan of action. By formulating such an action plan, healthcare providers can easily identify the issues that need to be more emphasized, topics that are not covered by anyone yet and prevent duplication of healthcare contents that are already available online. By ensuring e-health for all, we can contribute to implementing our UHC, as part of Sustainable Development Goals (SDG). Materials and Methods: In order to showcase the importance of digital technology in healthcare, we picked up two social media platforms that provide the highest possible healthcare information on adolescence and reproductive health and aim to reduce the rate of maternal mortality and morbidity to the bare minimum. Since the inception of the Facebook page called ‘Dr. Purabi’sHelp Desk https://www.facebook.com/DrPurabisHelpDesk/’ and the YouTube channel ‘Nowsheen Purabi, https://www.youtube.com/user/drpurabihelpdesk’ in November 2012, these online platforms have been delivering video contents, articles on adolescent-maternal-reproductive health, contraception, non-communicable disease prevention, vaccination, nutrition, and mental health.The data we have shown are taken from the analytics/ insights of Facebook page ‘Dr. Purabi’s Help Desk’ and YouTube channel ‘Nowsheen Purabi’. For Facebook page data, we have used the monthly insight report that Facebook provides every page owner. On the other hand, the YouTube data was taken from the channel analytics, which gives a lifetime data to the channel owner. Results: People from reproductive age (18-34 years old) mostly watch the YouTube contents, while same in Facebook Page. 64% men are somehow likely to be active in watching healthcare contents online. Contents are viewed by people from different parts of the world (Bangladesh 88%, India 8%, Saudi Arabia 1%, USA 1%, and Australia 1%). Almost 91% of the viewer uses their mobile phones; 6% use computers and 3% percent use tablets to watch the contents. 94% male and 6% females are engaged in the posts. Conclusion: If we can take necessary steps to engage more people in digital healthcare by lowering the internet price, we will be able to achieve SDG as well as UHC within a short time. We need the coordination of government and private initiatives to bridge the information gap between the healthcare professionals and the patients. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 201-206